Integrating efficacy and safety of vedolizumab compared with other advanced therapies to assess net clinical benefit of ulcerative colitis treatments: a network meta-analysis. (3rd June 2021) - Jairath, Vipul; Chan, Keith; Lasch, Karen; Keeping, Sam; Agboton, Christian; Blake, Aimee; Patel, Haridarshan
ABSTRACT: Objectives : Because only one head-to-head randomized trial of biologics for moderate-to-severe UC has been performed, indirect treatment comparisons remain important. This systematic review and network meta-analysis examined efficacy and safety of biologics and tofacitinib for moderate-to-severe UC, using vedolizumab as reference. Methods : Relevant studies (N = 19) of vedolizumab, adalimumab, infliximab, golimumab, ustekinumab, and tofacitinib were identified. Study design differences were addressed by assessing efficacy outcomes conditional on response at maintenance initiation. Primary analysis used fixed-effect models to estimate odds ratios for efficacy and safety endpoints. Results : Compared with vedolizumab 300 mg, adalimumab 160/80 mg was associated with less clinical remission (odds ratio, 0.69 [95% credible interval, 0.54–0.88]), and infliximab 5 mg/kg was associated with more clinical remission (1.67 [1.16–2.42]) and response (1.63 [1.15–2.30]). Adalimumab 40 mg, golimumab 50 mg, and ustekinumab 90 mg Q12W had significantly lower clinical remission rates during maintenance (0.62 [0.45–0.86], 0.55 [0.32–0.95], and 0.59 [0.35–0.99]) versus vedolizumab 300 mg Q8W. Response results were similar. Tofacitinib 10 mg had the highest maintenance treatment efficacy estimates and highest infection risk. Conclusion : Network meta-analysis and novel integrated benefit-risk analysis suggest a potentially favorable efficacy-safety balance for vedolizumab vs adalimumab and other advanced UC therapies.